The Implementation of Journal Writing In Englsh Teaching on Islamic Boarding School of DDI Mangkoso (An Experimental Research) - Zakiah Awaliah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The objective of the research was to find out the improvement of the students’ writing ability through using journal writing as a technique teaching in English teaching in second grade in term of content and organization. The researcher conducted a pre-experimental design with pre-test and post-test as instrument. The subject of research was the second grade of Senior High School on Islamic Boarding School of DDI Mangkoso. The result of the analysis showed that there was significant difference between pre-test and post-test. The mean score of post-test in content item (77.7) was greater than mean score of pre-test (56.75). And the mean score of post-test in organization item (79) was greater than mean score of pre-test (59.20). The t-test value of content was greater that t-table value (9.61 > 2.069). Then, t-test value of organization was greater than t-table value (8.80 > 2.069), and degree of freedom (df) = 23. It is said that the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. Therefore, the researcher concluded that there was significant difference between the students’ writing ability before and after using journal writing in English teaching, and it is said that journal writing as a technique teaching was effective to improved students’ writing ability at second grade of Senior High School on Islamic Boarding School of DDI Mangkoso.